Taurine Administration Counteracts Aging-Associated Impingement of Skeletal Muscle Regeneration by Reducing Inflammation and Oxidative Stress - Alessandra Barbiera; Silvia Sorrentino; Damon Fard; Elisa Lepore; Gigliola Sica; Gabriella Dobrowolny; Luca Tamagnone; Bianca Maria Scicchitano (MDPI AG, 2022)
Sarcopenia, which occurs during aging, is characterized by the gradual loss of skeletal muscle mass and function, resulting in a functional decline in physical abilities. Several factors contribute to the onset of sarcopenia, including reduced regenerative capacity, chronic low-grade inflammation, mitochondrial dysfunction, and increased oxidative stress, leading to the activation of catabolic pathways. Physical activity and adequate protein intake are considered effective strategies able to reduce the incidence and severity of sarcopenia by exerting beneficial effects in improving the muscular anabolic response during aging. Taurine is a non-essential amino acid that is highly expressed in mammalian tissues and, particularly, in skeletal muscle where it is involved in the regulation of biological processes and where it acts as an antioxidant and anti-inflammatory factor. Here, we evaluated whether taurine administration in old mice counteracts the physiopathological effects of aging in skeletal muscle. We showed that, in injured muscle, taurine enhances the regenerative process by downregulating the inflammatory response and preserving muscle fiber integrity. Moreover, taurine attenuates ROS production in aged muscles by maintaining a proper cellular redox balance, acting as an antioxidant molecule. Although further studies are needed to better elucidate the molecular mechanisms responsible for the beneficial effect of taurine on skeletal muscle homeostasis, these data demonstrate that taurine administration ameliorates the microenvironment allowing an efficient regenerative process and attenuation of the catabolic pathways related to the onset of sarcopenia.